Um jogo adaptativo para potencializar processos cognitivos de jovens com transtornos no desenvolvimento - Moura, Mariza de Souza (Universidade Federal Rural do Semi-Árido, 2017)
Digital technologies have been expanding its applicability, significantly in several fields, including mental health. The study developed by the Program “Oficinando em Rede” uses Information and Communication Technologies (ICT) promoting care, social insertion and training in mental health and education. Thus, ideas and projects concerning experiences with young people bearers of developmental disorder were made feasible to be studied and developed, through contact with a digital technology. Games act not only as entertainment but also, and especially, in the empowerment of cognitive processes of the young people who use them. In this experiment, there are various modes of applicating games in the scope of mental health and one of them happens during the workshops, that were conducted as regular activities, as actions by this university extension program, the “Oficinando em Rede”. Workshops that take place with children and teenagers who are inserted in the activities of the Center for Psychosocial Care of Children and Adolescents in Mossoró - RN (CAPSi). As an essential factor for the research, the project operated based on the observation of the characteristics demonstrated by each of those children and teenagers, among the coordination of behaviors, such as: gestures, ideas and emotions, especially while they were in contact with the digital games that were used in the workshops. It has been realized, during these workshops, that the same game, rouses different reactions in each of them, for their own actions, emotions and disorders that express themselves in a unique way during each experience. Based on a chart, containing the devices and elements that draw the attention of the young participants on the project, also by reading the logbooks developed in each workshop, and finally, through the use of categories that were perceived as a listing the specific game’s devices, such as sound, image, animation, cooperativity, among others, it have been made possible to notice which reactions were presented by the young people during the workshops, and with this experience came an idea of developing a game containing devices and adaptive elements, including the characteristics that attract attention of these participants in the project . The game follows a perspective of serious games, which are games created according to a specific purpose, by use of techniques and methods of games, but for a purpose that goes beyond fun or entertainment. And, yet, adaptive methods, which aid in the ability of the game to modify itself from the reactions of the young person during the act of playing. It is proposed, then, the development of an adaptive game to enhance the cognitive processes of children and teenagers with mental development disorder
Keywords: Saúde mental; Jogos adaptativos; Serious games; Processos cognitivos; Mental health; Adaptive games; Serious games; Cognitive processes; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO